The Relationship Between Teacher Well-being and Teaching Quality in the Learning Process at SD IT Kamiliyah Palembang - Annisa R, Mutiara; Risma Diana; Ayu Riski; Vivi Silviana; Afriantoni, Afriantoni (The Future of Education Journal, 2025)
This study aims to examine the relationship between teacher well-being and the quality of instructional guidance in the learning process at SD IT Kamiliyah Palembang. Employing a mixed methods approach, data were collected through questionnaires administered to 24 teachers and semi-structured interviews with 6 teachers. Quantitative results showed that teacher well-being was rated high (mean 83.3%), while the quality of instructional guidance was categorized as very good (mean 85.3%). Pearson correlation analysis revealed a positive and significant relationship between teacher well-being and instructional quality (r = 0.72, p < 0.01). Qualitative findings supported these results, indicating that teachers who felt psychologically and socially well demonstrated high enthusiasm and creativity in managing learning. This study highlights the importance of improving teacher well-being as a strategy to enhance the quality of education.